Maternal Heart Rate Variability during the First Stage of Labor - Musa, Shaza M.; Adam, Ishag; Hassan, Nada G.; Rayis, Duria A.; Lutfi, Mohamed F. (Frontiers in Physiology, 2017)
Labor necessitates continuous adjustments of cardiac autonomic reflexes by alternate activation of the sympathetic and parasympathetic nervous systems. The division of the autonomic nervous system that predominates during the first stage of labor is unclear and needs to be further investigated. The study aimed to compare heart rate variability (HRV) in pregnant women in the third trimester with those during the first stage of labor. We conducted a case–control study at Saad Abul Ela Maternity Hospital, Khartoum, Sudan. Forty-five women with singleton, live neonates in the first stage of labor and 45 women in the third trimester (but not in labor) were enrolled as case and control groups, respectively. Data on the medical history, obstetrics history, and clinical examinations that were performed in all of the studied women were obtained using prearranged questionnaires. Cardiac autonomic modulation (CAM) of the heart was examined in both groups based on time and frequency domain HRV indices. There were no significant differences in age, parity, body mass index, and hemoglobin levels between the two groups. Pregnant women in labor had significantly higher LnSDNN, LnRMSSD, LnTP, LnVLF, LnLF, LnHF, LF Norm, and LnLF/HF ratio, but lower HF Norm compared with controls (P < 0.001). These findings remained unchanged when possible confounders were controlled for using regression analysis. Our findings suggest a significant increase in indictors of sympathetic CAM, namely LF Norm and LnLF/HF, during labor. Sympathetic hypertonia associated with labor is unlikely to increase the risk of cardiac events because sympathetic CAM simultaneously increases with global HRV. Increased HRV during labor may be explained by parasympathetic activation as indicated by higher LnHF and LnRMSSD at the time of delivery.